Implementation of the SIAP Desa Application To Improve Public Services In Pao-Pao Village, Tanete Rilau District, Barru Regency - Nurlia, Nurlia; Samsibar, Samsibar (LPPPIPublishing, 2024)
This research aims to determine: Implementation of public services based on the Village SIAP application in Pao-Pao Village, Tanete Rilau District, Barru Regency. And to find out the supporting factors in implementing public services based on the Village SIAP application in Pao-Pao Village, Tanete Rilau District, Barru Regency. The method used in this research is qualitative, data collection techniques consist of participant observation, in-depth interviews and documentation studies. The results of this research show that the ease of use of the Village SIAP application in Pao-Pao Village can reduce manual service procedures that can take hours to just a few minutes. The supporting factors in implementing public services based on the Village SIAP application are training in application operation, community participation, government support, the existence of computer equipment and a WiFi network at the village office.